Explaining Agricultural Distortion Patterns The Roles of Ideology, Inequality, Lobbying and Public Finance - Dutt, Pushan (The World Bank, 2009)
In this paper, the authors examine the political economy drivers of the variation in agricultural protection, both across countries and within countries over time. The paper starts by listing the key insights provided by both the theoretical and empirical literature on the political economy of trade policy formulation. The authors then set out a basic framework that allows us to put forth various testable hypotheses on the variation and evolution of agricultural protection. The authors find that both the political ideology of the government and the degree of income inequality are important determinants of agricultural protection. Thus, both the political-support-function approach as well as the median-voter approach can be used in explaining the variation in agricultural protection across countries and within countries over time. The results are consistent with the predictions of a model that assumes that labor is specialized and sector-specific in nature. Some aspects of protection also seem to be consistent with predictions of a lobbying model in that agricultural protection is negatively related to agricultural employment and positively related to agricultural productivity. Public finance aspects of protection also seem to be empirically important